FAKTOR YANG MENJADI DAYA TARIK KOPI âJOSSâ DI JALAN WONGSODIRJAN KOTA YOGYAKARTA - , PRIYAGUNG SAMBODO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Urbanization in urban areas is increasing every year due to fewer jobs in the village . This resulted in many emerging informal sector in urban areas. Informal sector as street vendor ( PKL ) is in great demand . Street Vendors affects visualization of Yogyakarta , aside from the location of the many traders were on the pavement so disturbing public order . Street Vendors in Yogyakarta is that many traders angkringan . Angkringan center in Yogyakarta is famous bustling Angkringan Kopi \" Joss \" north Tugu Station . This study aims to identify the phenomena diAngkringan Kopi \" Joss \" as the place visited . This study uses deductive and qualitative approaches . Deductive method with authors collected qualitative theory that will become a reference . The data is taken from field observations by distributing questionnaires , interviewed visitors , and documenting Events on the ground . This study suggests that the factor is the main attraction at the Kopi \" Joss \" instead of a Public Open Space facilities are provided. Fascination is in Kopi \" Joss \" is a comfort factor , which has long history , the price of food is cheap , convenient location , unique culinary and advertising resources or the incentive to do . Another thing that makes kopi \" Joss \" is widely known because it has the Image Identity is already embedded in the public mind that the location of Kopi \" Joss \" only in Wongsodirjan street or Station Tugu Yogyakarta .